SOME ISSUES OF CRIMINALISTIC CHARACTERISTICS OF WATER POLLUTION - VYATKIN Andrey Nikolaevich (Правовое государство: теория и практика)
The article considers various aspects of the term «criminalistic characteristics of the crime» in order to identify the essential features of the criminalistic characteristics, which have an applied value for a particular category of crime – water pollution, the liability for which is provided for by Article 250 of the Criminal Code of the Russian Federation. Methods: comparative, analytical, scientific generalisations. Results: the article proposes a structure for the criminalistic characteristics of water pollution, including the object, method, crime situation and the identity of the criminal. The article reveals specific features of the crime situation: low level of legal consciousness of society in general and employees of controlling and law enforcement bodies in particular, imperfection of regulatory framework and high level of corruption, which should be taken into account when organising investigation of water pollution.